Kif14 Mutation Causes Severe Brain Malformation and Hypomyelination - Fujikura, Kohei (Public Library of Science, 2013)
We describe a novel spontaneous mouse mutant, laggard (lag), characterized by a flat head, motor impairment and growth retardation. The mutation is inherited as an autosomal recessive trait, and lag/lag mice suffer from cerebellar ataxia and die before weaning. lag/lag mice exhibit a dramatic reduction in brain size and slender optic nerves. By positional cloning, we identify a splice site mutation in Kif14. Transgenic complementation with wild-type Kif14-cDNA alleviates ataxic phenotype in lag/lag mice. To further confirm that the causative gene is Kif14, we generate Kif14 knockout mice and find that all of the phenotypes of Kif14 knockout mice are similar to those of lag/lag mice. The main morphological abnormality of lag/lag mouse is severe hypomyelination in central nervous system. The lag/lag mice express an array of myelin-related genes at significantly reduced levels. The disrupted cytoarchitecture of the cerebellar and cerebral cortices appears to result from apoptotic cell death. Thus, we conclude that Kif14 is essential for the generation and maturation of late-developing structures such as the myelin sheath, cerebellar and cerebral cortices. So far, no Kif14-deficient mice or mutation in Kif14 has ever been reported and we firstly define the biological function of Kif14 in vivo. The discovery of mammalian models, laggard, has opened up horizons for researchers to add more knowledge regarding the etiology and pathology of brain malformation.